La scolarisation, moyen de lutte contre la pauvreté ? - Sophie Lewandowski (Les éditions de la Maison des sciences de l'Homme, 2007)
Burkina Faso, under structural adjustment for several decades, has been made the echo of the speeches of the World Bank concerning the fight against poverty. In spite of a rhetorical integration of multidimensional designs of poverty and of the question of inequalities, these speeches remain primarily founded on an economicist approach of the world. In this context, the educational policies, presented like centers major fight against poverty, are based on the theory of the "human capital" for which the individual, central actor, is supposed to be free, rational and calculator. In spite of "participative" consultations seeking a democratic legitimation, these designs are opposed to those of the "recipients". According to certain Gourmantchés of Gnagna for example, schooling is perceived like a factor of impoverishment and by others like a possibility of enrichment. Moreover, poverty is seen like a total and multidimensional state which the person can enter and of which it can leave according to her relationship with the group, which remains the dominant entity. Schooling then represents a rather collective opportunity that individual, of which the very diversified uses obey complex rules of security and of redistribution.